An Efficient Cluster Head Selection and Routing in Mobile WSN - S.V, Manikanthan; T, Padmapriya (International Journal of Interactive Mobile Technologies (iJIM), 2019)
Wireless Sensor Networks (WSN) includes numerous sensor nodes that are connected to each other through the use of wireless short distance links. The transfer of data between the individual nodes is found to be energy-constrained and the energy-efficient protocol in WSNs is a huge requirement. In addition, the deployment of large numbers of sensor nodes increases the size of the network, which in turn increases the energy consumption rate. An efficient protocol is developed in this research that includes grid-based mobile communication network formation, efficient path selection through cluster head selection and data communication. In addition, multi-stage authentication is implemented to provide security from source node to destination node for the transfer of data. Implementation is performed via NS2-based platform and the result obtained shows that the proposed system outperforms other existing techniques in terms of packet delivery and use of energy through network lifetime.